Stylo-Textual Strategies in Psalm 51 - Agbeleoba, Samuel (International Journal of Language and Literary Studies, 2024)
Psalm 51, attributed to King David, stands as a profound expression of repentance and restoration within the biblical tradition. This paper presents a thorough examination of the stylo-textual strategies employed in Psalm 51, focusing on its linguistic, stylistic, and textual dimensions. Through meticulous analysis, the study reveals the intricate interplay between rhetorical devices, linguistic features, and textual structures in conveying the psalmist’s plea for divine mercy and spiritual renewal. Stylistically, the psalm employs parallelism, imagery, repetition, metaphor, and irony to evoke emotional resonance and rhetorical impact. Textually, the psalm unfolds a coherent structure, progressing from confession to petition and affirmation, reflecting the psalmist’s journey from contrition to transformation. Moreover, the psalmist’s engagement with textual traditions and cultural norms enriches the text’s interpretive depth and theological significance. Through this analysis, readers gain deeper insights into the stylo-textual strategies employed in Psalm 51, inviting reflection on its enduring relevance and profound insights into the human experience of sin, forgiveness, and redemption.